PEMBELAJARAN KOOPERATIF METODE CONCEPT MAPPING UNTUK MENINGKATKAN KONSEP DIRI PESERTA DIDIK DI SMK KUBURAYA - Rahmawati, Dian; Jamiah, Yulis; B.S, Dian Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractSelf-concept of X Akuntansistudents at SMK Panca Bhakti Sui Rayawere still unsatisfied. This research wasconductedto determine whether therewas an effect on students?self-concepts taught using concept mapping method of cooperative learningcompared toconventional learning model or not, and to determine effectsize of concept mapping method of cooperative learning towardstudents? self-concept. This research usedquasi experimental with One Group Pretest-Posttest Design. The research sample wasclass X Akuntansi. The data collection tool used is self-concept questionnaire consist 12 statement. Based on pre-questionnaire and post-questionnaire data analysis using the Linear Regression Analysis, the correlation coefficient obtained was 0.4478 and measured significant. The linear regression equation obtained was  means that the effect was linear and positive. The effect size was calculated from the determination coefficient (0.2005) so the method gave 20,05% effect to students? self-concept. Concept mapping method of cooperative learninggave1.79% effecttowardacademic confidence indicator and 1.12% toward academic effort indicator. Keywords:  Concept Mapping Method, Coperative Learning, Self-Concept